Cervical Debranching in the Endovascular Era: A Single Centre Experience. (July 2019) - Konstantinou, Nikolaos; Debus, Eike S.; Vermeulen, Christine F.W.; Wipper, Sabine; Diener, Holger; Larena-Avellaneda, Axel; Kölbel, Tilo; Tsilimparis, Nikolaos
Abstract : Objective/Background: Debranching of the supra-aortic arteries is a common practice either as part of a hybrid treatment of aortic arch pathology or owing to arterial occlusive disease. Results of the debranching techniques have not been reported frequently. Methods: This was a retrospective single centre study of all consecutive patients with cervical debranching procedures as part of hybrid aortic arch repair. Results: Between 2010 and 2017, 201 patients underwent 211 cervical debranching procedures in a tertiary centre. Mean ± SD patient age was 67.7 ± 10.7 years (70.6% males; n = 142/201) and mean ± SD body mass index (BMI) was 26.3 ± 5. In 78.7% of the cases carotid–subclavian bypass was performed alone ( n = 166/211) followed by transposition of the subclavian artery to the ipsilateral carotid ( n = 17/211; 8.1%) and in 28 cases (13.3%) a combination of procedures was performed. Twenty-four cases (11.4%) were complicated with local bleeding and 21 cases required re-intervention (10.4%). Nineteen patients (9.5%) developed local peripheral neurological damage post-operatively. Eight patients (3.8%) developed a chylous fistula and five (2.4%) presented with a local wound infection. One patient (0.5%) developed a bypass graft infection. The thirty day mortality was 7.6% ( n = 16/211): one death occurred after isolated debranching without thoracic endovascular aneurysm repair (TEVAR; 0.5%). Whether the hybrid procedures were undertaken in a single stage (simultaneous TEVAR and cervical debranching) or two stage fashion appeared to have a significant impact on 30 day mortality (single stage n = 9/60 [15%] vs. debranching alone or two stage hybrid procedures n = 7/144 [4.9%]; p = .018). The major stroke incidence was 4.3% ( n = 9/211); no strokes occurred after isolated debranching. Stroke was correlated with longer operating times (odds ratio [OR] 1.006; 95% confidence interval [CI] 1.000–1.011; p = .045) and higher BMI (OR 1.195; 95% CI 1.009–1.415; p = .039). Mean ± SD follow up was 15 ± 17 months (range 0–89 months). Primary cumulative graft patency during follow up was 98.1% (n = 207/211) and secondary patency was 100%. Conclusion: The results of cervical debranching procedures showed not only excellent patency rates, but also a significant rate of local complications. Carotid–subclavian bypass appeared to be safer with significantly fewer post-operative complications. Staged hybrid procedures also seemed to be safer.